2021
DOI: 10.1007/s11886-021-01483-6
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging for Cardiac Evaluation in Patients with COVID-19

Abstract: Purpose of Review A growing number of cardiovascular manifestations resulting from the novel SARS-CoV-2 coronavirus (COVID-19) have been described since the beginning of this global pandemic. Acute myocardial injury is common in this population and is associated with higher rates of morbidity and mortality. The focus of this review centers on the recent applications of multimodality imaging in the diagnosis and management of COVID-19-related cardiovascular conditions. Recent Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…48 Thus, appropriate use of a multimodality imaging strategy is most useful to detect ACI and distinguish MI from myocarditis, TTC, pulmonary embolism and other cardiac and chest pathologies in COVID-19 patients. 49,50…”
Section: Differential Diagnosismentioning
confidence: 99%
“…48 Thus, appropriate use of a multimodality imaging strategy is most useful to detect ACI and distinguish MI from myocarditis, TTC, pulmonary embolism and other cardiac and chest pathologies in COVID-19 patients. 49,50…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Echocardiography has further refined our understanding of myocardial damage in COVID-19, detailing certain functional patterns of injury [ 14 ]. Szekely and colleagues found right ventricular (RV) dysfunction to be the most common echocardiographic abnormality in a series of 100 hospitalized COVID-19 patients, among nearly 40%, with RV deterioration most associated with clinical decompensations [ 43 ].…”
Section: Part I: Acute Infectionmentioning
confidence: 99%
“…Early case reports described a spectrum of cardiovascular manifestations of COVID-19 infection, including myocarditis, stress cardiomyopathy, myocardial infarction (MI), and arrhythmia [ 9 – 12 ]. In combating a novel disease, the cardiology community deployed its most advanced technology including cardiac magnetic resonance imaging (CMR) which has characterized acute and chronic consequences of SARS-CoV-2 infection [ 13 , 14 ], but often the findings have left clinicians with more questions than answers.…”
Section: Introductionmentioning
confidence: 99%
“…Transthoracic echocardiography (TTE) is the most used imaging modality for cardiac evaluation in COVID-19 as it is can be easily performed at the patient's bedside, providing information about cardiac structure and function [133]. One survey showed that the most common indications for TTE among 1216 examined COVID-19 patients were suspected heart failure, cardiac biomarker elevation and right-sided heart failure (Table 1) [134].…”
Section: Noninvasive Imaging 431 Echocardiographymentioning
confidence: 99%
“…Moreover, another study showed that the most common findings on TTE were right ventricular (RV) dilation and dysfunction in 39%, followed by left ventricular diastolic dysfunction in 16% and left ventricular systolic dysfunction in only 10% of COVID-19 patients examined within 24 h of admission [128]. A right ventricular impairment that is associated with poor outcomes may be due to extensive use of mechanical ventilation and positive end-expiratory pressures for ARDS patients, as well as hypercoagulability, which both cause damage to lung parenchyma and pulmonary microvasculature resulting in pulmonary hypertension [133,136]. According to a study that included 120 COVID-19 patients right ventricular longitudinal strain (RVLS) is a strong predictor of higher mortality in patients with COVID-19, as patients with impaired RV strain are more prone to ARDS development needing high flow oxygen therapy and mechanical ventilation [137].…”
Section: Noninvasive Imaging 431 Echocardiographymentioning
confidence: 99%